The savvy musician 2.0 amplifying impact, income, and inspiration - Cutler, David 1971- (Oxford scholarship online, 2025)
David Cutler's groundbreaking book 'The Savvy Musician' shaped a generation of artists. Now, 'The Savvy Musician 2.0' expands the realm of possibility. In a world where constant change is the only guarantee, innovative problem-solving is as important as excellence. This comprehensive, inspirational resource, which showcases 150+ case studies of diverse performers, creators, educators, and institutions, unveils actionable strategies to guide readers toward unprecedented success